A cutting-plane method with internal iteration points for the general convex programming problem - I. Ya. Zabotin; K. E. Kazaeva; O. N. Shulgina (Учёные записки Казанского университета: Серия Физико-математические науки)
A cutting method for solving the problem of convex programming was proposed. The method calculates iteration points based on approximation by polyhedral sets of the constraint region and the epigraph of the objective function. Its distinguishing feature is that the main sequence of approximations is constructed within the admissible region. At each step, it is also possible to assess how close the current value of the function is to the optimal value. The convergence of the method was proved. A few of its implementations were outlined.